2019
DOI: 10.2478/pjct-2019-0039
|View full text |Cite
|
Sign up to set email alerts
|

Examination of steam gasification of coal with physically mixed catalysts

Abstract: The aim of this study was to analyse the steam gasification process of ‘Janina’ coal with and without Na-, K- and Ca-catalysts. The catalysts were physically mixed with the coal due to the simplicity of this method, short time of execution and certainty that the amount of catalyst is exactly as the adopted one. The isothermal measurements were performed at 800, 900 and 950°C and a pressure of 1 MPa using thermovolumetric method. The obtained results enabled assessment of the effect of analysed catalysts on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…One can be observed that the share of calcium oxide, considered compounds that catalyse the gasification process [32], is the highest (above 40%). The ash also contains other catalytically active components (e.g., oxides of iron, potassium, magnesium and sodium [33,34]), but their shares are low. On the other hand, over 1/3 of the ash consists of compounds that have an adverse effect on gasification reaction, such as Al 2 O 3 , SiO 2 or P 2 O 5 [35,36].…”
Section: Characteristic Of Rdfmentioning
confidence: 99%
“…One can be observed that the share of calcium oxide, considered compounds that catalyse the gasification process [32], is the highest (above 40%). The ash also contains other catalytically active components (e.g., oxides of iron, potassium, magnesium and sodium [33,34]), but their shares are low. On the other hand, over 1/3 of the ash consists of compounds that have an adverse effect on gasification reaction, such as Al 2 O 3 , SiO 2 or P 2 O 5 [35,36].…”
Section: Characteristic Of Rdfmentioning
confidence: 99%